PH‐Dependent Anticancer Drug Release from Silk Nanoparticles. Issue 12 (26th April 2013) - Seib, F. Philipp; Jones, Gregory T.; Rnjak‐Kovacina, Jelena; Lin, Yinan; Kaplan, David L.
Abstract Silk has traditionally been used as a suture material because of its excellent mechanical properties and biocompatibility. These properties have led to the development of different silk‐based material formats for tissue engineering and regenerative medicine. Although there have been a small number of studies about the use of silk particles for drug delivery, none of these studies have assessed the potential of silk to act as a stimulus‐responsive anticancer nanomedicine. This report demonstrates that an acetone precipitation of silk allows the formation of uniform silk nanoparticles (98 nm diameter, polydispersity index 0.109), with an overall negative surface charge (–33.6 ± 5.8 mV), in a single step. Silk nanoparticles are readily loaded with doxorubicin (40 ng doxorubicin/μg silk) and show pH‐dependent release (pH 4.5≫ 6.0 > 7.4). In vitro studies with human breast cancer cell lines demonstrates that the silk nanoparticles are not cytotoxic (IC50 > 120 μg mL−1) and that doxorubicin‐loaded silk nanoparticles are able to overcome drug resistance mechanisms. Live cell fluorescence microscopy studies show endocytic uptake and lysosomal accumulation of silk nanoparticles. In summary, the pH‐dependent drug release and lysosomal accumulation of silk nanoparticles demonstrate the ability of drug‐loaded silk nanoparticles to serve as a lysosomotropic anticancer nanomedicine.